Eyegames : easy and fun visual exercises, an occupational therapist and optometrist offer activities to improve vision! - Hickman, Lois.; Hutchins, Rebecca E. (Arlington, TX : Sensory World, 2010)
Designed by an OT and an optometrist,'Eyegames' offers practical, playful activities designed to improve visual skills in both adults and children.
The development of vision -- Problems of visual perception -- Vision and autism -- Guide to eyegame activities -- Eyegame activities -- Computers and vision -- Is sooner always better? -- Losing sleep? Light may be the culprit.
'An OT and optometrist offer activities to improve vision'-- Cover.
Includes bibliographical references and glossary.
Keywords: Ocular motility disorders